User Satisfaction with Library Facilities and Services of College Libraries Affiliated to Dr. B.A.M. U. Aurangabad in Osmanabad District: A Survey - Balbhim Shaiwale, Shailesh (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
This study focused on user satisfaction with the library facilities and services provided by the fifteen college libraries in Osmanabad district affiliated to Dr. B.A.M.U Aurangabad. The primary and secondary literature is rarely analyzed to assess the user’s response to various aspects of the library’s rooms, collections, services, and staff. There is scope for further improvement in the "overall satisfaction" of visitors. This research will help definitely to understand the current status of college libraries and also it will help to identify areas for improvement.
Keywords: College library; learning resource center (LRC); library object; user satisfaction; user survey